Is Functional Literacy a Prerequisite for Entering the Labor Market? An Analysis of Determinants of Adults Literacy and Earnings in Ghana - Blunch, Niels-Hugo; Verner, Dorte (World Bank, Washington, DC, 2015)
The authors analyze the determinants of literacy and earnings in Ghana. They link literacy and earnings with various other factors, including age, gender, family educational background, distance to school, and income. Literacy and age are negatively correlated, suggesting that efforts to strengthen the supply and quality of basic education programs in recent years have succeeded in raising literacy rates. Parents' education is positively associated with literacy. Distance to the nearest primary school, residence in a rural area, and poverty are negatively associated with literacy. Functional literacy appears to be a prerequisite for entering the labor market, which may partly explain the lack of returns to education other than middle school and technical and professional training. The policy implications of this study: Basic education and literacy programs should target girls and poorer households, especially in rural areas.